2(3w+2)-12=3w-11

Simple and best practice solution for 2(3w+2)-12=3w-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3w+2)-12=3w-11 equation:


Simplifying
2(3w + 2) + -12 = 3w + -11

Reorder the terms:
2(2 + 3w) + -12 = 3w + -11
(2 * 2 + 3w * 2) + -12 = 3w + -11
(4 + 6w) + -12 = 3w + -11

Reorder the terms:
4 + -12 + 6w = 3w + -11

Combine like terms: 4 + -12 = -8
-8 + 6w = 3w + -11

Reorder the terms:
-8 + 6w = -11 + 3w

Solving
-8 + 6w = -11 + 3w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-3w' to each side of the equation.
-8 + 6w + -3w = -11 + 3w + -3w

Combine like terms: 6w + -3w = 3w
-8 + 3w = -11 + 3w + -3w

Combine like terms: 3w + -3w = 0
-8 + 3w = -11 + 0
-8 + 3w = -11

Add '8' to each side of the equation.
-8 + 8 + 3w = -11 + 8

Combine like terms: -8 + 8 = 0
0 + 3w = -11 + 8
3w = -11 + 8

Combine like terms: -11 + 8 = -3
3w = -3

Divide each side by '3'.
w = -1

Simplifying
w = -1

See similar equations:

| 6r+2=56 | | 2x+x+x=180 | | 3(w-6)-5w=-36 | | h=-5t^2+60t | | 7x+3x+90=180 | | -16t^2+24t+3=12 | | X^3-9x^2+20x-12=0 | | 3x(x-9)= | | 3+2t=13 | | 5x-2= | | 3x^3+3x^2-11x-10=0 | | 4.2(x-1)=9.8 | | (x)(x)(x)+4(x)(x)-25x-100=0 | | 25x-10= | | x^2+5x=x(x-11) | | -12=-7-3.5s | | 7xy+1xy=72 | | (x)(x)(x)+4(x)(x)-100=0 | | 6x+10= | | n=wsv | | 7(a+1)-3a=5+4(a-1) | | 2(x-7)=3 | | -18y=da | | 1.33x+2=-1 | | 1.33+2=-1 | | 2*-8.5+13.6=0.4*-8.5 | | 5(3-t)-(3-3t)=5 | | 8x^6+6x^3+7=0 | | 3x+11=25 | | r^2-15r+54=0 | | 4x+10y-8+4x-4y= | | x^2-x-110=0 |

Equations solver categories